Children's political participation in Peru: on the road to their recognition as political subjects - Castillo Valverde, Alejandra (2021)
This article presents a reflection on the progress in the recognition of children as political subjects. To this end, it introduces the right to participation present in the Convention on the Rights of the Child and its scope, as well as the scarcity of spaces for participation and the limitations they present. Based on an investigation of the Children's Councils in the municipalities of Lima and Miraflores in Peru, characteristics are presented on the citizen awareness of the councilors based on the analysis of three components: awareness of rights, awareness of responsibility and sense of belonging to a community. It is found that they have a sense of belonging to the group of children with whom they share characteristics, problems and interests and recognize their role as important to represent this group. Similarly, the potentialities and limitations of this program to ensure effective participation are identified. Finally, the implications of recognizing children as political subjects from a political science perspective are explored, mentioning their importance for rethinking public policies, civic education, citizenship studies and the potential for political change.